A qualitative investigation of staff's practical, personal and philosophical barriers to the implementation of a web‐based platform in a child mental health setting. Issue 3 (4th July 2017) - Town, Rosa; Midgley, Nick; Ellis, Louise; Tempest, Rebecca; Wolpert, Miranda
Abstract: Aim: To provide an understanding of the factors that discouraged staff members from using a new web‐based platform (CAMHSweb) with young people in a child and adolescent mental health service (CAMHS). Although evidence‐based service improvement technology like CAMHSweb is becoming more common in child mental health, the staff‐level barriers to the use of web‐based platforms have not been explored in depth in the literature. Method: Semi‐structured interviews with six employees were carried out in a London‐based child mental health service that a preliminary audit had identified as having a poor utilisation of the platform. All participants had previously been invited to use the platform as part of their clinical work. Results were analysed using thematic analysis (Braun and Clarke, 2006). Findings: Three overarching themes covered staff's practical, personal and philosophical barriers to implementation. Interviewees believed that CAMHSweb was too challenging to implement, that it was not an asset to therapists, and that it interfered with the therapeutic process. Discussion and Implications: These findings provide a nuanced understanding of the multiple factors that may discourage clinicians from using web‐based platforms. This may have implications for researchers or practitioners who aim to design or implement technology in child mental health services.